Sistem Informasi Perpustakaan Berbasis Web Application - Irawan, Yudie; Mustafid, Mustafid; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Digital  library  system  contributes  the  development  of  digital  resource  digital  resource  that  can  be accessed  via the  Internet.  Librarymanagement system contributed to the development of automation membership data processing, circulation and cataloging. In this thesisis  to develop  a new  concept of  digital  library  systems  and  library  management  system  by  integrating  these  two systems  architecture. Integration  architecture  implemented  by  inserting  component  library  management  system  into  the  digital  library  system  architecture. Web application technology required for these components in order to be integrated with the digital library system components.  The newsystem  has  the advantage  of  this  development  application  utilization  of  borrowing,  membership  and  kataloging  to  a  sharable  over the internet,  so  applications  that  can  be used  together.  Information  can be  delivered  between the  library  catalog,  without  leaving the  digitallibrary function in the utilization of shared digital resources derived from uploading by each librarian.Keywords : Digital library system; Library management system; Web application